Pengembangan Media Virtual Reality (VR) pada Materi Sistem Organ di SMP Kelas VIII - Putri, Septia Eka; Hendri, Nofri; Yusri, Meldi Ade Kurnia; Masnur, Alkadri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to develop Virtual Reality (VR) based learning media on the material of the human organ system for eighth-grade junior high school students. This study employs research and development (R&D) methods using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The learning media is developed using the Millealab application and implemented with the assistance of VR Box devices. Data was collected through expert validation sheets (materials and media), practicality questionnaires, and learning outcome tests for students. The data obtained was analyzed descriptively quantitatively to determine the level of validity, practicality, and effectiveness of the developed media. The research results showed that the developed VR media is valid, practical, and effective in improving students' learning outcomes. Thus, this VR media is suitable to be used as an innovative alternative in science learning, particularly for the material of organ systems.